Green and Low-Carbon Transformation of China's Chemical and Petrochemical Industry - Houliang Dai; Jianfeng Chen; Qingtang Yuan; Peicheng Liu (中国工程科学)
The chemical and petrochemical industry is one of the pillar industries of the national economy. However, the energy and resource consumption, "three wastes" (i.e., waste gas, waste water, and industrial residue), and carbon emissions of the industry are large. Therefore, it is inevitable to accelerate the green and low-carbon transformation of the industry, thus to achieve high-quality industrial development and strengthen the petrochemical sector. This study analyzes the basic situation of the green and low-carbon transformation of the chemical and petrochemical industry from the perspectives of international consensus, domestic requirements, raw material changes, market constraints, technological evolution, and intelligent transformation. It also sorts out the development status of China's chemical and petrochemical industry from the aspects of industrial scale, industrial structure, resource utilization, pollutant emission, carbon emission, and industrial science and technology, and further reviews the prominent problems that restrict the green and low-carbon transformation of the industry. Moreover, the study proposes the key tasks for the green and low-carbon transformation of the industry, including innovation in green and low-carbon technologies; green transformation of the industrial structure; innovation in environment-friendly products; carbon peaking in key areas; green and low-carbon transformation for energy use; green, low-carbon, and clean production; digital and intelligent transformation; and green production demonstration; this aims to achieve a high-end industrial structure, low-carbon energy consumption, cyclic utilization of resources, clean production processes, green supply of products, and digital production mode. To this end, it is suggested that we should actively and steadily promote the carbon peaking and carbon neutralization goals, achieve carbon peaks in subdivided fields by stages, steadily promote the green transformation of the energy sector, and promote green and low-carbon transformation with active policies, thereby ensuring the green and low-carbon transformation of China's chemical and petrochemical industry.